Representações docentes: constituindo o ser professora de língua portuguesa - Clein, Paola Talite (2018)
This study describes and analyzes representations of a teacher's Portuguese Language group from public schools that teach in schools that mostly meet students from rural contexts of two counties in the southwest of Paraná. The interpreted discursive productions are about many aspects that are part of the teaching work activity. In order to understand how the discursive-ideological constitution of the teacher's work occurs, we compare the discursive productions with each other, describing and understanding the guiding aspects of the teaching practice by the fact of the representations presented by the research participants. The analysis corpus compiles data generated from the application of a written questionnaire (composed of open questions) and the recording of interactions in the Portuguese class during the teaching practice (totaling seventeen hours of audio recording class). This research is qualitative / interpretative and assumes as a research method the ethnographic case study (ANDRÉ, 2005). The theoretical apparatus that gave support to the work was guided by contributions from Applied Linguistics, Cultural Studies and Education. The results obtained in the analysis of the data suggest that the teaching work is constituted by a set of aspects of several orders, such as theoretical-practical, didactic, cultural and ideological. And that, in addition, representations undergo continuous transformations by being in a scenario of intersection between culturally established models of teacher and the new representations that are being constructed through the practices of language. This research, as well as other studies that are part of Applied Linguistics, is justified by the important role played by this science in studying social life from the specific practices, instruments and institutions in which human action develops. Thus, this research proposes a critical reflection on Portuguese teaching issues and their representations, as well as contribute to the advancement in the discussions about the teaching work in its discursive constitution.